MRI of patients with implanted cardiac devices. Issue 3 (4th August 2017) - Kalb, Bobby; Indik, Julia H.; Ott, Peter; Martin, Diego R.
Abstract : Cardiac implanted electronic devices (CIEDs) have historically been regarded as a contraindication for performing magnetic resonance imaging (MRI), limiting the availability of this exam for large numbers of patients who may have otherwise benefited from the unique diagnostic capabilities of MRI. Interactions between CIEDs and the magnetic field associated with MRI systems have been documented, and include potential effects on CIED function, lead heating, and force/torque on the generator. Several device manufacturers have developed "MR‐Conditional" CIEDs with specific hardware and software design changes to optimize the device for the MR environment. However, a substantial body of evidence has been accumulating that suggests that MRI may be safely performed in patients with either conditional or nonconditional CIEDs. Institutional policies and procedures, including preexam screening and assessment by skilled electrophysiology personnel and intraexam monitoring, allow MRI to be safely performed in CIED patients, as evidenced by at least two, large multicenter prospective studies and multiple smaller, single‐institution studies. Cross‐departmental collaboration and a robust safety infrastructure at sites that perform MRI should allow for the safe imaging of CIED patients who have a clinical indication for the study, regardless of the conditionality status of the device. Level of Evidence : 5 Technical Efficacy : Stage 5 J. Magn. Reson. Imaging 2018;47:595–603.